2015
DOI: 10.1002/car.2393
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Maternal Childhood Emotional Abuse/Neglect and Parenting Outcomes: A Systematic Review

Abstract: The relationship between maternal childhood emotional abuse/neglect and parenting outcomes: A Systematic Review. AbstractThis paper reviews the evidence concerning the association between reported maternal childhood experience of emotional abuse and/or neglect and subsequent parenting outcomes. Relevant studies were identified through a systematic search of four electronic databases using a pre-determined keyword search. Reference lists of included papers were reviewed and key authors in the field contacted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 34 publications
5
49
0
2
Order By: Relevance
“…While specific types of trauma, such as physical abuse, sexual abuse, or neglect, have been studied in relation to future parenting practices (Bert et al 2009 ; Hughes and Cossar 2016 ; Lyons-Ruth and Block 1996 ), there has been limited research specifically on the totality of ACEs in relation to parenting stress and practices (Chung et al 2009 ; Steele et al 2016 ). Additionally, though studies have focused on specific forms of childhood trauma and later parenting practices, the maximum age at which these acts of trauma can occur often vary by study.…”
Section: Introductionmentioning
confidence: 99%
“…While specific types of trauma, such as physical abuse, sexual abuse, or neglect, have been studied in relation to future parenting practices (Bert et al 2009 ; Hughes and Cossar 2016 ; Lyons-Ruth and Block 1996 ), there has been limited research specifically on the totality of ACEs in relation to parenting stress and practices (Chung et al 2009 ; Steele et al 2016 ). Additionally, though studies have focused on specific forms of childhood trauma and later parenting practices, the maximum age at which these acts of trauma can occur often vary by study.…”
Section: Introductionmentioning
confidence: 99%
“…12 ACEs have also been explicitly linked with dysfunctional parent-child interactions and with parenting attitudes and behaviors. 13,14 Finally, parent ACEs may contribute to vulnerable living conditions, such as food insecurity, 13,15 as well as higher risk of ACEs among the children themselves. 16,17 The potential intergenerational effects of ACEs are supported by research revealing increased risk of adverse health outcomes among children of parents who experienced chronic trauma.…”
mentioning
confidence: 99%
“…Although the vast majority of mothers who have experienced previous victimization do not abuse their own children (Hughes & Cossar, 2015), victimization history may increase the risk of parenting difficulties (Ehrensaft et al, 2015;Chiesa et al, 2018). A multi-method, multi-informant prospective study conducted among a community-based sample in the U.S. demonstrated that parents who were physically and/or sexually abused as children later had difficulties in multiple domains of parenting (Ehrensaft et al, 2015).…”
Section: Relation Between Violence Victimization and Parentingmentioning
confidence: 99%
“…The authors posit that parents with a history of maltreatment may evidence emotional distancing from the child and a limited ability to impose structure, leading to impairments in their parenting. Similarly, a recent review concluded that mothers who experienced emotional abuse and neglect are more likely to have difficulties with several aspects of parenting, including dysfunctional parent-child interactions, lower empathy and acceptance, greater psychological control, and increased punitiveness (Hughes & Cossar, 2015). Commensurate findings are present for mothers experiencing IPV.…”
Section: Relation Between Violence Victimization and Parentingmentioning
confidence: 99%